FAKTOR-FAKTOR YANG MEMPENGARUHI ETIKA PENGGELAPAN PAJAK - Hustianto Sudarwadi; Khezya Melani Christy; Desirianingsih H. Parastri (Cakrawala Management Business Journal, 2021)
This study aims to determine the effect of tax discrimination, tax knowledge, subjective norms, love of money on the ethics of tax evasion in the perception of individual taxpayers in Manokwari Regency. The source of data used in this study is primary data, namely data obtained directly from respondents by distributing questionnaires. The questionnaire used in this study was developed from research conducted by (Rahman, 2013); (Khasanah, 2014); (Fatimah and Wardani, 2017); (Noviriyani, 2020). The population in this study were all Individual Taxpayers registered at the end of 2020 at the Manokwari KPP Pratama West Papua Province totaling 83,354 Individual Taxpayers. The sampling technique in this research is probability sampling with simple random sampling method. The number of samples used is 347 samples. The analysis used in this research is using multiple linear regression analysis which is processed using SPSS version 22 program. The results show that Tax Discrimination, Subjective Norms and Love of Money have a positive effect on the ethics of tax evasion in the perception of individual taxpayers, while Tax Knowledge has a negative effect on the ethics of tax evasion in the perception of individual taxpayers. Keywords: Tax Discrimination, Subjective Norms, Love of Money, Tax Evasion Ethics